The Impact of Work-Life Balance and Stress on Millennial Turnover: The Mediation of Job Satisfaction - Hendi Anggoro; Tri Harsini Wahyuningsih; Alga Aprila Dwi Purwito (Telaah Bisnis, 2026)
In this study, the researchers analyse whether work-life balance and work stress affect the intention of millennial workers in the Karawang Industrial Area to quit their jobs, with job satisfaction as the factor bridging that relationship. This study conducted this research using non-probability and purposive sampling methods on all millennial workers in the Karawang Industrial Area. There were 143 participants. We collected data by distributing questionnaires. We conducted instrumental tests, normal distribution tests, and classical hypothesis tests, all of which met the criteria. This study uses regression analysis and Process 4.2, a macro analysis program for SPSS 26 developed by Andrew F. Hayes, to verify the hypothesis. This study found that both work-life balance and stress significantly and positively affect employees' intention to quit. These two factors also have a significant positive impact on employee job satisfaction, thereby reducing the intention to quit. It was also revealed that job satisfaction acts as a mediator between work-life balance and stress on the intention to quit. Overall, 70.4% of the variation in the intention to quit can be explained by work-life balance, stress, and job satisfaction, while 29.6% is influenced by other variables outside the scope of the study.